How ultrafast X-ray pulses can reveal hidden secrets of photosynthesis. (1st April 2019) - Bergmann, Uwe; Yachandra, Vittal; Yano, Junko
Abstract : X-ray-based techniques are extremely versatile and can provide information regarding the atomic arrangement of atoms in a molecule and are often the method of choice for exploring the structures of proteins and their ligands. The photosynthetic splitting of water and evolution of molecular oxygen by plants and cyanobacteria is one of the key reactions in nature, which is catalysed by a metal site in a membrane-bound photosynthetic protein complex. In this article, we will describe how X-ray pulse lasers can simultaneously probe the overall atomic structure of the photosynthetic system and the electronic structure of a catalytic metal site under physiological conditions in real time.